Problematika Perceraian Dan Pemenuhan Nafkah Anak - Burhanudin, Achmad Asfi; Muhammad Al Faruq; Moch. Azis Qoharuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Marriage according to Law No. 1 of 1974 is an innate bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the One Godhead. However, it is not uncommon in marriage to have continuous disputes and quarrels as well as other causes that sometimes cause a situation that causes a marriage to be unsustainable and must be divorced. When divorce occurs, usually the problem is regarding the child, who takes care of him and who bears the cost of his maintenance. Therefore, it is necessary to study the legal principles regarding the obligation of male parents for legal child support after the occurrence of divorce. The legal principle of the obligation to provide child support after a divorce, whether in national laws and regulations, Islamic law, or in customary law, imposes this obligation on male parents. But even though they have been punished to pay alimony after divorce, many do not comply. The cause is the economic factor of male parents, male parents have remarried, female parents are able to provide for children. There are no clear rules regarding the determination of the nominal amount of child support and firm and clear legal sanctions against parents who are proven to have neglected their obligations or have bad intentions to hide their ability to provide for themselves. Basically, negligence in child support can be applied for execution by the Court, but procedural difficulties and the amount of costs that must be incurred cause an imbalance between the value of alimony demanded and the costs that must be incurred. Moreover, to pay and use the services of an expensive advocate to become a lawyer in child support claims, people are unable to get legal assistance from experts and professionals to fight for their rights